Development of Codular-Based Mathbox Media to Improve Students’ Self-assessment and Understanding of The Pythagorean Theorem - Siti Maria Ulfa; Mohammad Mahfud Effendi; Rizal Dian Azmi (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This study uses 'Mathbox' media which is focused and aims to improve students' self-assessment and understanding and is developed using the Codular website. The research method used is Research and Development (RD) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development of this learning media proved to be valid with an average percentage of 95.45% of the 'Very Good' Media Checker criteria as measured using the Guttmann scale. There was an 11.1% increase in the pre-test to post-test self-assessment scores which were measured using a Likert scale. The difference in the scores of students' understanding tests with the Paired T-test shows that the application of media affects students' understanding test scores. Based on the results obtained, it can be concluded that the designed Kodular web-based Mathbox media is a valid medium and can improve students' self-assessment and understanding of the Pythagorean theorem.Penelitian ini menggunakan media 'Mathbox' yang difokuskan dan bertujuan untuk meningkatkan penilaian dan pemahaman diri siswa, serta dikembangkan menggunakan website Codular. Metode penelitian yang digunakan adalah Research and Development (RD) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Pengembangan media pembelajaran ini terbukti valid dengan persentase rata-rata 95,45% kriteria validasi media 'Sangat Baik' yang diukur menggunakan skala Guttmann. Ada peningkatan 11,1% pada skor self-assessment pre-test hingga post-test yang diukur dengan menggunakan skala Likert. Perbedaan nilai tes pemahaman siswa dengan Paired T-test menunjukkan bahwa penerapan media berpengaruh terhadap nilai tes pemahaman siswa. Berdasarkan hasil yang diperoleh, dapat disimpulkan bahwa media Mathbox berbasis web Kodular yang dirancang merupakan media yang valid dan dapat meningkatkan penilaian diri dan pemahaman siswa terhadap teorema Pythagoras.